2008
DOI: 10.4314/ari.v3i3.40785
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Crude Oil And Its Products On Bilirubin Of African Catfish <i>Clarias gariepinus</i>

Abstract: The study was aimed at determining the effect of Crude oil and its product on bilirubin of a Catfish Fishes w th an average weight of 21.08 ± 0.12g were subjected to the toxic and recovery phases o d f erent concentrat ons (0.2 ml/L, 0.4 ml/L, 2.0 ml/L. and 4 ml/L) of Crude oil, d esel, kerosene and petrol for 4 days and 26 days respectively. The bilirubin level of fishes subjected to different concentrations of toxicants was higher than that of the control. The biochemical parameters investigated showed sign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…Increased total bilirubin level is indicative of metabolic problems in the liver such as reduced hepatocyte uptake or impaired bilirubin conjugation" [30]. Nwamba et al [31] demonstratedincreased levels of bilirubin in fish exposed to crude oil as that seen in the present study. The authors observed that total bilirubin concentrations increased with increasing concentration of crude oil.…”
Section: Discussionsupporting
confidence: 64%
“…Increased total bilirubin level is indicative of metabolic problems in the liver such as reduced hepatocyte uptake or impaired bilirubin conjugation" [30]. Nwamba et al [31] demonstratedincreased levels of bilirubin in fish exposed to crude oil as that seen in the present study. The authors observed that total bilirubin concentrations increased with increasing concentration of crude oil.…”
Section: Discussionsupporting
confidence: 64%
“…The limiting of oxygen supply through this process leads to asphyxiation in the organism which finally culminates in death [14]. One method by which crude oil and its products cause damage to aquatic organisms is that oxygen is not soluble in them and therefore limits the amount of oxygen made available to the water body from the atmosphere [15]. Petroleum products penetrate into the metabolic pathways of aquatic animals and thereby alter the metabolic action of the affector sites and hence exert their action on the exposed organism [13].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also observed similar findings with respect to total bilirubin levels as reported in the present work. Nwamba et al (2006) reported increased levels of bilirubin in fishes exposed to crude oil. It was also observed that total bilirubin concentrations was dose-dependant crude oil concentrations.…”
Section: Resultsmentioning
confidence: 99%